ChemInform Abstract: Cu‐Catalyzed Chemoselective Preparation of 2‐(Pinacolato)boron‐Substituted Allylcopper Complexes and Their in situ Site‐, Diastereo‐, and Enantioselective Additions to Aldehydes and Ketones. Issue 40 (12th September 2013) - Meng, Fanke; Jang, Hwanjong; Jung, Byunghyuck; Hoveyda, Amir H.
Abstract The complexes are efficiently generated by base‐promoted reaction in the presence of bisphosphine ligands and coupled in situ with the carbonyl compounds.